IL-8 and WISP1 in the molecular characteristics of malignant ascites in ovarian cancer - T. V. Abakumova; D. R. Dolgova; S. S. Pirmamedova; I. I. Antoneeva; S. O. Gening; I. A. Ivanchenko; T. P. Gening (Медицинская иммунология, 2024)
An unfavorable prognosis for ovarian cancer is associated with metastasis to the peritoneum and the formation of malignant ascites, which contains factors affecting the growth and survival of tumor cells. Molecular and functional analysis of ascites provides information both for clinical diagnosis and for understanding the mechanisms of progression and resistance in ovarian cancer. The aim of the study was to evaluate the levels of IL-8 and WISP1 in the acellular portion of ascites in advanced ovarian cancer. In 30 patients diagnosed with ascitic ovarian cancer stage III-IV according to FIGO, before treatment, the levels of IL-8 (Kit A-8762, Interleukin-8-ELISA-BEST, JSC Vector-Best, Russia) and WISP1 (Kit SEG895Hu CloudClone Corp., China) were determined (pg/mL). Based on the results of the effectiveness of chemotherapy according to the TP scheme, all patients were divided into the following groups: without relapse, relapse-free period up to 6 months – early relapse and progression during chemotherapy. Statistical processing was carried out using Statistica 13. Analysis of patient progression-free time was carried out using the Cox regression method, and the patient survival function was assessed using the Kaplan-Meier method (Jamovi 2.4.14). We found that the level of IL-8 in the acellular part of malignant ascites in ovarian cancer in patients without relapse is significantly lower than in the early relapse group (176.58 (139.68-217.01) pg/mL versus 320.43 pg/mL (250.49-369.81), p = 0.019). The level of WISP1 was significantly increased in the acellular part of ascites only in patients with progression during chemotherapy (980.51 (796.61-1524.15) pg/mL versus 770.55 (500.60- 1254.90) pg/mL in patients without relapse and 764.09 (581.55-823.38) pg/mL in patients with relapse). We found a positive strong Pearson correlation between IL-8 and WISP1 in ascites in a group of patients without relapse (r = 0.783, p = 0.012). In the multivariate version of Cox regression, the risk of relapse increases by 1.01 (1.01-1.02, p = 0.001) times with an increase in the level of IL-8 in the acellular part of ascites. When IL-8 levels in the acellular portion of ascites are above 225 pg/mL, the median progression-free time in patients with advanced ovarian cancer is 11.7 (5.2-18.2, 95% CI) months.Thus, increased levels of IL-8 and WISP1 in malignant ascites in ovarian cancer are associated with a shorter progression-free time. IL-8 in malignant ascites activates Wnt/β-catenin signaling in advanced ovarian cancer.